THE NEXUS OF FINANCIAL DEVELOPMENT AND ECONOMIC GROWTH ACROSS EMERGING ECONOMIES (The South East European Journal of Economics and Business, 2022)
The relationship between financial development and economic growth has been discussed in the literature, but there is no consensus on it. This study aims to examine the relationship between financial development and economic growth in terms of developing countries. The data of 19 developing countries were analyzed individually in an attempt to reveal which of the views explaining the relationship between financial development and economic growth is predominantly valid. In the analysis, the bounds test developed by Pesaran et al. (2001) was used to determine the cointegration relationship, and the Toda Yamamoto causality test (1995) was used to determine the causality relationship. As a result, causality was determined from economic growth to financial development in four countries and from financial development to economic growth in four countries. In 11 countries, no causality was found. The results support the view that no approach is valid for every country.